Étudier les phénomènes émotionnels en classe : au carrefour des neurosciences et des recherches en éducation - Victoria PROKOFIEVA; Jean-Luc VELAY
In order to improve educational research focusing especially on such complex themes as the influence of emotions on the learning processes in class, collaboration between Educational studies and Neurosciences appears particularly relevant. However, the road to such interdisciplinary research is full of potholes and obstacles. They are particularly due to the intertwining of the theoretical and methodological approaches of both fields, but also to the multidimensional character of the experimental context which is at the same time a school situation as well as to the complexity of emotional phenomenon itself. Finally, the difficulties of an experimental study in class are discussed along with some suggestion how to overcome its difficulties and to put in perspective its results so to improve our knowledge about school learning and educational practices applied in class.